International Financial Statistics, November 2011. (International Financial Statistics; International Financial Statistics ;, 2011)
The IMF's principal statistical publication, International Financial Statistics (IFS) Online, is the standard source of international statistics on all aspects of international and domestic finance. For most countries, IFS Online reports data on balance of payments, international investment position, international liquidity, monetary and financial statistics, exchange rates, interest rates, prices, production, government accounts, national accounts, and population. Updated monthly.